The Opportunity Cost of the Conservation Reserve Program: A Kansas Land Example - Taylor, Mykel R.; Hendricks, Nathan P.; Sampson, Gabriel S.; Garr, Dillon (My University, 2020)
The effects of the Conservation Reserve Program (CRP) on farmland values is investigated using a set of parcel-level data for land sales in Kansas over the period 1998 to 2014. The sales data are used to estimate a hedonic model of land values that allows for the opportunity cost of CRP enrollment to vary across space and time. Factors impacting the opportunity costs include the relative productivity of land, returns to farming, and the time remaining under the CRP contracts. We find that the discount associated with having land under CRP contract averages 7%.
Keywords: Conservation Reserve Program; CRP; Land Values